Perbandingan Batasan Usia Perkawinan dalam Hukum Keluarga Islam (Studi Komparasi Negara Indonesia, Mesir dan India) - Nasution, Ahmad Yani; Jazuli, Moh. (Prodi Hukum Ekonomi Syariah (Muamalah), 2024)
The objective of this study was to investigate the marriage age limits in Indonesia, Egypt, and India. Research on age limits in marriage is crucial due to the social and cultural implications of child marriage. The methodology employed is qualitative, utilizing library research. Furthermore, a comparative approach evaluates and contrasts the marriage laws of the three nations concerning age limits. The comparative analysis employs vertical, horizontal, and diagonal methodologies. The research material comprises legislative documents and pertinent academic literature. The results indicate that family laws in Indonesia, Egypt, and India prohibit child marriage. Vertically, Indonesia's marriage age remains unaffected by the Shafi'i school, establishing a minimum of 15 years, whereas Egypt follows the Hanafi madzhab with a minimum age of 18. In India, the authors contend that the influence of the Hanafi madzhab is negligible, particularly as proposed legislation seeks to elevate the marriage age for women to 21. Additionally, horizontal comparisons highlight the distinctions in laws regarding the legality, procedures, and ramifications of marriage in each nation.